Wildlife in U.S. Cities: Managing Unwanted Animals - John Hadidian (Animals, 2015)
Conflicts between people and wild animals in cities are undoubtedly as old as urban living itself. In the United States it is only of late, however, that many of the species now found in cities have come to live there. The increasing kind and number of human-wildlife conflicts in urbanizing environments makes it a priority that effective and humane means of conflict resolution be found. The urban public wants conflicts with wildlife resolved humanely, but needs to know what the alternative management approaches are, and what ethical standards should guide their use. This paper examines contemporary urban wildlife control in the United States with a focus on the moral concerns this raises. Much of the future for urban wildlife will depend on reform in governance, but much as well will depend on cultural changes that promote greater respect and understanding for wild animals and the biotic communities of which they and we are both a part.